TINJAUAN KUAT LENTUR BALOK KOMPOSIT KAYU - Alves, Paulito M. D.; Sina, Dantje A. T.; Cornelis, Remigildus (Jurnal Teknik Sipil, 2013)
This research was use wood beam, reinforced concrete plate and nail as shear connector. Nail that used is artless nail and thread nail that public reside in marketing. the purpose of this research is to know bending strength of a composite beam of wood-concrete with shear connector artless nail and shear connector thread nail. The research was conducted at the Laboratory of Concrete Civil Engineering Department University of Nusa Cendana Kupang - NTT and Laboratory of Mechanical Engineering State Polytechnic of Kupang - NTT. From the results of research and analysis of the data obtained the maximum tension of composite beam with shear connector artless nail : maximum load as big as 40000 N; bending moments as big as 5.01 x106 Nmm; tension depresses as big as 29,327 N/mm2; contact surface-tension as big as 3,545 N/mm2; bending stress as big as 16,381 N/mm2; the shear stress as big as 6,325 N/mm2. Whereas the average test results of composite beams with shear connector thread nail is obtained by maximum load as big as 51667 N; bending moment as big as 6.47 x 106 Nmm ; tension depresses as big as 38,400 N/mm2; contact surface-tension as big as 4,624 N/mm2; bending stress as big as 21,205 N/mm2; the shear stress as big as 8,036 N/mm2.